Pharmacotherapeutic interventions for bipolar disorder type II: addressing multiple symptoms and approaches with a particular emphasis on strategies in lower and middle-income countries. (12th December 2019) - Godman, Brian; Grobler, Christoffel; Van-De-Lisle, Marianne; Wale, Janney; Barbosa, Wallace Breno; Massele, Amos; Opondo, Philip; Petrova, Guenka; Tachkov, Konstantin; Sefah, Israel; Abdulsalim, Suhaj; Alrasheedy, Alian A.; et al.
ABSTRACT: Introduction : Appropriately managing mental disorders is a growing priority across countries in view of the impact on morbidity and mortality. This includes patients with bipolar disorders (BD). Management of BD is a concern as this is a complex disease with often misdiagnosis, which is a major issue in lower and middle-income countries (LMICs) with typically a limited number of trained personnel and resources. This needs to be addressed. Areas covered : Medicines are the cornerstone of managing patients with Bipolar II across countries including LMICs. The choice of medicines, especially antipsychotics, is important in LMICs with high rates of diabetes and HIV. However, care is currently compromised in LMICs by issues such as the stigma, cultural beliefs, a limited number of trained professionals and high patient co-payments. Expert opinion : Encouragingly, some LMICs have introduced guidelines for patients with BD; however, this is very variable. Strategies for the future include addressing the lack of national guidelines for patients with BD, improving resources for mental disorders including personnel, improving medicine availability and patients' rights, and monitoring prescribing against agreed guidelines. A number of strategies have been identified to improve the treatment of patients with Bipolar II in LMICs, and will be followed up.